2016
DOI: 10.1021/acs.est.5b04465
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Energy-Water Usage Efficiency of the Reuse of Treated Municipal Wastewater for Artificial Groundwater Recharge

Abstract: This project investigates the energy-water usage efficiency of large scale civil infrastructure projects involving the artificial recharge of subsurface groundwater aquifers via the reuse of treated municipal wastewater. A modeling framework is introduced which explores the various ways in which spatially heterogeneous variables such as topography, landuse, and subsurface infiltration capacity combine to determine the physical layout of proposed reuse system components and their associated process energy-water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
0
19
0
1
Order By: Relevance
“…In an energy-water nexus analysis of water supply scenarios in coastal communities (Tampa Bay and San Diego) in the USA, maximizing water reclamation was found to be a better solution compared to desalination from embodied energy, greenhouse gas (GHG) emissions and energy cost perspectives [19]. However, a study of the energy requirements needed to deliver reclaimed water up-gradient of six watersheds indicated that the water needed for the energy exceeded the amount of water that would be pumped to the various delivery locations [20]. Another study considering the Middle East and North Africa showed a relatively weak dependence of energy systems on seawater (rather than fresh water) but a strong dependence of water systems (mainly abstraction and production) on energy [21].…”
Section: Introductionmentioning
confidence: 99%
“…In an energy-water nexus analysis of water supply scenarios in coastal communities (Tampa Bay and San Diego) in the USA, maximizing water reclamation was found to be a better solution compared to desalination from embodied energy, greenhouse gas (GHG) emissions and energy cost perspectives [19]. However, a study of the energy requirements needed to deliver reclaimed water up-gradient of six watersheds indicated that the water needed for the energy exceeded the amount of water that would be pumped to the various delivery locations [20]. Another study considering the Middle East and North Africa showed a relatively weak dependence of energy systems on seawater (rather than fresh water) but a strong dependence of water systems (mainly abstraction and production) on energy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Steinel et al [33] considered existing infrastructure, such as dams, to select sites suitable for the infiltration of captured surface runoff. The optimum surface spreading basin was evaluated using a weighted overlay analysis model in a porous aquifer in the USA [34]. Farhadian et al [35] used the Nash conflict resolution method to determine suitable sites for MAR application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, site selection has included hydraulic conductivity [34], storativity [18], and transmissivity [27] of the aquifers studied. The thickness of the aquifer has also been included in some studies [33,38].…”
Section: Transmissivitymentioning
confidence: 99%
“…Numerous studies have investigated different aspects of planning MAR or recycled water systems, but none presented comprehensive engineering and economic methods suited to our study's scope on multisupply spreading basin design. Representative recent studies have focused on optimizing existing water infrastructure systems (Cherchi et al, ; Perelman et al, ), optimizing designs for nonpotable recycled water systems (Kavvada et al, ; Lee et al, ), designing direct potable reuse systems (Guo & Englehardt, ; Vitter et al, ), siting and costing new recharge facilities (Dillon & Arshad, ; Fournier et al, ; Pedrero et al, ; Russo et al, ), optimizing recharge and recovery well systems that receive storm water (Clark et al, ; Marchi et al, ), and optimizing new recycled water distribution systems (Fournier et al, ; Lan et al, ; Lee et al, ; Zhang et al, ). In addition, several studies—for example, Newman et al (), Porse et al (), Wu et al (), and Xiong et al ()—investigate optimizing urban water supplies portfolios that include recycled water, but none of these studies consider both the engineering and economic considerations within our study's scope.…”
Section: Introductionmentioning
confidence: 99%